Carpology of the genus Tragopogon L. (Asteraceae) - Sukhorukov, Alexander P.; Nilova, Maya (Phytotaxa, 2015)
67 species of Tragopogon were investigated with regard to fruit anatomy. The outer achenes, especially the beak and the central part of the seed-containing body, provide the most valuable features (diameter and outlines of the body and the beak, and arrangement of the mechanical elements in the body parenchyma). Some specimens of widely distributed taxa (e.g. T. capitatus, T. dubius, T. pratensis, T. pseudomajor) show variation in the character set and require more investigation prior to further taxonomic treatment. The species studied are classified into informal groups to demonstrate the diversity of carpological traits within the genus, and a comparison is made with the existing molecular phylogeny. The separation of the genus Geropogon from Tragopogon is supported by the achene anatomy.